Creating positive parental influence in 4-H competitions: A guide for 4-H Volunteers - Deborah L. Nistler; Kate Fogarty (EDIS)
4H 8.5, a 4-page fact sheet by Deborah L. Nistler and Kate Fogarty, introduces a “4-As” framework for understanding parent motivations for participation in competitive youth programs, and suggests approaches for volunteers to use to encourage parent engagement. Includes references. Published by the UF 4-H Youth Development Program, December 2008.